Palladium(0) catalyzed Suzuki cross-coupling reaction of 2,5-dibromo-3-methylthiophene: selectivity, characterization, DFT studies and their biological evaluations - Rizwan, Komal; Zubair, Muhammad; Rasool, Nasir; Mahmood, Tariq; Ayub, Khurshid; Noorjahan Banu, Alitheen; Muhammad Nazirul Mubin, Aziz; Akhtar, Muhammad Nadeem; Nasim, Faiz-ul-Hassan; Bukhary, Snober Mona; Ahmad, Viqar Uddin; Rani, Mubeen (Springer Open, 2018)
Thiophene derivatives have shown versatile pharmacological activities. The Suzuki reaction proved a convenient method for C–C bond formations in organic molecules. In the present research work novel derivatives of 2,5-dibromo-3-methylthiophene (3a–k and 3l–p) has been synthesized, via Suzuki coupling reaction in low to moderate yields. A wide range of functional groups were well tolerated in reaction. Density functional theory investigations on all synthesized derivatives (3a–3p) were performed in order to explore the structural properties. The pharmaceutical potential of synthesized compounds was investigated through various bioassays (antioxidant, antibacterial, antiurease activities). The compounds 3l, 3g, 3j, showed excellent antioxidant activity (86.0, 82.0, 81.3%), respectively by scavenging DPPH. Synthesized compounds showed promising antibacterial activity against tested strains. 3b, 3k, 3a, 3d and 3j showed potential antiurease activity with 67.7, 64.2, 58.8, 54.7 and 52.1% inhibition at 50 µg/ml. Results indicated that synthesized molecules could be a potential source of pharmaceutical agents.